Commentary on "What are the experiences of professionals working with parents with learning disabilities? A meta-ethnography". Issue 1 (22nd February 2021) - MacIntyre, Gillian; Stewart, Ailsa
Abstract : Purpose: The purpose of this paper is to provide a commentary on Pytlowana and Stenfert Kroese's article on the experiences of professionals working with parents with learning disabilities by exploring challenges and good practice in this area. Design/methodology/approach: Key areas of practice were identified for further exploration by drawing on research studies with parents with learning disabilities. Findings: While there is growing evidence of good practice around working with parents with learning disabilities, a number of challenges around communication and relationship-based practice remain. The paper recommends further training and education for those working in this complex area of practice. Originality/value: The paper adds value by bringing together evidence from across a number of studies to highlight good practice.